Combined assessment of left atrial volume parameters for predicting recurrence of atrial fibrillation following pulmonary vein isolation in patients with paroxysmal atrial fibrillation. Issue 5 (25th March 2019) - Soga, Fumitaka; Tanaka, Hidekazu; Mochizuki, Yasuhide; Mukai, Jun; Suto, Makiko; Takada, Hiroki; Hatani, Yutaka; Matsuzoe, Hiroki; Hatazawa, Keiko; Sano, Hiroyuki; Ooka, Junichi; Shimoura, Hiroyuki; et al.
Abstract: Objectives: Our aim was to test the hypothesis that comprehensive simplified left atrial (LA) assessment derived from routine echocardiography may be more useful than assessment of LA volume alone for predicting atrial fibrillation (AF) recurrence after pulmonary vein isolation (PVI). Methods: We studied 156 patients with paroxysmal AF (PAF) who had undergone PVI. Echocardiography was performed within two days before PVI. Maximum (Max‐LAVi) and minimum LA volume index (Min‐LAVi) were calculated with the biplane modified Simpson's method, and then normalized to the body surface area. On the basis of previous findings, the predefined cutoff value of Max‐LAVi for AF recurrence was set at Max‐LAVi ≥ 34 mL/m 2 . ΔLA volume index (ΔLAVi) was also calculated as Max‐LAVi minus Min‐LAVi. The follow‐up period after PVI was 24 months. Results: AF recurrence was observed in 35 patients. Multivariate logistic regression analysis showed that ΔLAVi (odds ratio [OR]: 1.131; 95% confidence interval [CI]: 1.057‐1.221; P  < 0.001) was an independent predictor of AF recurrence. Sequential logistic regression models for predicting AF recurrence revealed that a model based on clinical variables including age, gender and AF duration ( χ 2  = 1.65) was improved by the addition of Max‐LAVi ≥ 34 mL/m 2 ( χ 2  = 13.8; P  < 0.001), and further improved by the addition of ΔLAVi ( χ 2  = 18.2; P  = 0.036). Of note is that only 1.02 ± 0.10 minutes per patient was needed to obtain a comprehensive LA assessment that included Max‐LAVi, Min‐LAVi, and ΔLAVi. Conclusion: This easy‐to‐use comprehensive simplified LA approach from routine echocardiography may well have clinical implications for better management of PAF patients.